A nomogram model based on tumor necrosis factor-like ligand 1A(TL1A) and death receptor-3(DR3) promoter methylation for predicting 90-day prognosis in patients with HBV-associated acute-on-chronic liver failure - Wei, Xue-Fei; Zhang, Feng; Zhu, Han-Xu; Tian, Zhe-Zhe; Xu, Miao-Miao; Fan, Yu-Chen; Wang, Kai (Frontiers in Molecular Biosciences, 2025)
PurposeAcute-on-chronic liver failure (ACLF) associated with hepatitis-B-virus (HBV) is a life-threatening condition characterized by severe hepatic dysfunction. The TL1A/DR3 signaling axis modulates immune responses and contributes to hepatic inflammation. This study aimed to investigate the methylation level of TL1A/DR3 promoter, explore its ability to predict prognosis, and establish a prognostic model combined with clinical indicators.MethodMethylation status and gene expression of TL1A and DR3 were analyzed in peripheral blood mononuclear cells (PBMCs) from 714 participants using Methylight and quantitative polymerase chain reaction (qPCR). Univariate, LASSO, and multivariate analyses were performed to identify key prognostic factors for 90-day outcomes in patients with HBV-associated acute-on-chronic liver failure (HBV-ACLF) and develop corresponding prognostic models. Model performance, including calibration and clinical utility, was evaluated using receiver operating characteristic (ROC) curves, Hosmer-Lemeshow (H-L) tests, and decision curve analysis (DCA). A visual nomogram was constructed to integrate these factors for risk stratification.ResultAnalysis revealed significantly reduced TL1A and DR3 promoter methylation in HBV-ACLF patients, correlating with impaired liver function and coagulation parameters. PBMCs from these patients showed elevated mRNA expression of TL1A, DR3 and IL-6 compared to other groups. Methylation levels of TL1A and DR3 demonstrated high sensitivity and specificity in predicting HBV-ACLF severity. Besides, non-survivors exhibited lower TL1A/DR3 methylation than survivors. A prognostic model integrating prothrombin time activity (PTA), procalcitonin (PCT), and TL1A/DR3 methylation demonstrated excellent performance in predicting 90-day outcomes.ConclusionAberrant TL1A/DR3 promoter methylation reflects the disease severity, and can serve as potential biomarkers for the risk assessment of HBV-ACLF.